2009
DOI: 10.1016/j.crohns.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate management of special situations in Crohn's disease (upper gastro-intestinal; extra-intestinal manifestations; drug safety during pregnancy and breastfeeding): Results of a multidisciplinary international expert panel—EPACT II

Abstract: EPACT II recommendations are freely available online (www.epact.ch). The validity of these criteria should now be tested by prospective evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…A multidisciplinary European expert panel (EPACT-II) convened in 2007 to develop explicit appropriateness criteria [20][21][22][23] regarding CD treatment. During an update meeting in October 2012, the panel evaluated when and under which conditions it was appropriate to consider withdrawal of CD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A multidisciplinary European expert panel (EPACT-II) convened in 2007 to develop explicit appropriateness criteria [20][21][22][23] regarding CD treatment. During an update meeting in October 2012, the panel evaluated when and under which conditions it was appropriate to consider withdrawal of CD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These clinical situations lead to several uncertain treatment indications, but probably reflect current trend in the management of perianal and complex fistulas [13,14]. However, the EPACT II panel results [5][6][7][8] show some disagreement with these above-mentioned clinical management strategies and recommend a more conservative approach. Appropriateness criteria will thus need to evolve constantly to keep up with the literature, but can, however, express other characteristics based on experts' votes.…”
Section: Discussionmentioning
confidence: 90%
“…In the event of disagreement (at least one vote falling in the lowest and one in the highest three-point region) between the experts, the corresponding clinical scenarios were considered uncertain [3]. The results of EPACT II have already been published [5][6][7][8] and are available online in a user-friendly manner (www.epact.ch) for use in clinical practice.…”
Section: Patientsmentioning
confidence: 99%
“…It is category C, but a number of reviews and studies found no increased risk of preterm delivery, spontaneous abortion, or major malformations with the drug, and the authors considered it safe during pregnancy [15][16][17]. An optional treatment for nongonococcal urethritis is ofloxacin [12•], but because it is category C, it is better to use macrolides (discussed below) for this condition during pregnancy.…”
Section: Fluoroquinolonesmentioning
confidence: 99%